1998
DOI: 10.3109/07420529808993201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study to Determine the Optimal Melatonin Dosage form for the Alleviation of Jet Lag

Abstract: To compare the impact of various dosage forms of melatonin and placebo on jet lag symptoms, 320 volunteers who had flights over 6 to 8 time zones were recruited for a double-blind, randomized, placebo-controlled study. The volunteers received either melatonin 0.5-mg fast-release (FR) formulation, melatonin 5-mg FR formulation, melatonin 2-mg controlled-release (CR) formulation, or placebo. The study medication was taken once daily at bedtime during 4 days after an eastward flight. The volunteers completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
2
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 18 publications
0
81
2
9
Order By: Relevance
“…However, when the time in the destination is expected to be brief (2 days or less), circadian adaptation may be counterproductive and treatment should be aimed at improving or alleviating jet-lag symptoms. 34 Nonpharmacologic treatment approaches are important in the management of jet-lag disorder. Strategic exposure and avoidance of exposure to light have been utilized as an effective treatment approach.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, when the time in the destination is expected to be brief (2 days or less), circadian adaptation may be counterproductive and treatment should be aimed at improving or alleviating jet-lag symptoms. 34 Nonpharmacologic treatment approaches are important in the management of jet-lag disorder. Strategic exposure and avoidance of exposure to light have been utilized as an effective treatment approach.…”
Section: Key Pointsmentioning
confidence: 99%
“…Estimations of core body temperature minimum are based upon known relationships with respect to habitual wake time, prompting one to estimate core body temperature minimum timing either 2 or 3 hours prior to sleep offset, depending upon whether one typically sleeps up to 7 hours or more than 7 hours, respectively. [24][25][26] Travel to the west generally favors phase delays, which can be achieved in approximately 2-hour increments (reflecting the greater ease of delaying the clock), by following similar principles. In the opposite pattern, subjects expose themselves to light for approximately 3 hours prior to the core body temperature minimum and avoid light for approximately three hours thereafter (see Figure 3 as an example).…”
Section: Timed Light Exposurementioning
confidence: 99%
“…24,25 Immediate-release preparations appear to perform better than controlled-release formulations. 26 Although most studies have examined the efficacy of melatonin for jet lag occurring subsequent to eastward travel, [26][27][28][29] a single study examined its use in travel to the west and found it to be efficacious. 25 Melatonin use has been studied using a variety of different dosing schedules.…”
Section: Nocturnal Medication Administration For Jet Lagmentioning
confidence: 99%
See 2 more Smart Citations